Do trees suppress grass fuel loads? : canopy cover effects in South African savannas - Donaldson, Jason (Department of Biological Sciences, 2017)
Continental scale analysis of the savanna biome indicated that fire did not spread at tree canopy cover above 40%. This study investigates this relationship in a field study. It is possible that the type of tree (forest vs. savanna) may influence the amount of shade experienced by the understory and therefore this study also explores differences in LAI between congeneric pairs of forest and savanna tree species. Data were collected in two major South African savanna parks. Plots were set out to measure grass biomass in reference to canopy cover in both Kruger National Park (n=60) and the Hluhluwe-iMfolozi Game Reserve (n=82). Seven congeneric pairs were selected to compare leaf area and LAI between forest and savanna tree species using a destructive method. Against expectations, it was only when canopy cover reached 80% that grass fuel load was too low to support fire spread in all Kruger National Park plots (Pr=O) and 89% of the Hluhluwe-iMfolozi Game Reserve plots (Pr=0.11). No consistent, general relationships were evident with leaf area or LAI in comparisons between forest-savanna congeneric pairs. The significance of these findings and future direction is discussed.